Folk medicine in Mandaguaçu municipality, Paraná State: an ethnobotanical approach=Medicina popular em Mandaguaçu, Estado do Paraná: uma abordagem etnobotânica - Gisele Caroline Novakowski; Patrícia de Nazaré Cardoso Furlanetto; Edmar Antônio Correa (Acta Scientiarum: Biological Sciences, 2012)
Herein, we present results from an ethnobotanical study (from February to August 2009) aiming the improvement and rationalization of medical practices, based on popular use of plants. We applied semi-structured interviews to 220 families from the urban area of Mandaguaçu municipality, Paraná State. During the interviews we recorded the following information about the used plants: common name; plant part used; method of preparation; collection site; therapeutic indication, and known adverse effects. Additionally, we compared the data obtained in the interviews with the literature in order to identify contradiction in use and application. Among the interviewees, 90% use medicinal plants, obtained especially from the backyards. We recorded 44 ethnobotanical citations, comprising 47 species (22 families). The species most frequently mentioned in the interviews were, respectively, Cymbopogon citrates (DC) Stapf. (Lemon grass), Mentha sp. (Mint), Plectranthus barbatus Andrews (False Boldo) and Plectranthus ornatus Codd (Dog bane). The applications most cited were: the treatment of diseases from the digestive tract (122 citations), respiratory (67 citations) and nervous system (40 citations). In general, the population knows the correct method for preparing the medicinal plants. However, they report that do not know any adverse effect caused by these plants. This scenario is worrying because some species are recognized in the literature as potentially toxic or responsible for adverse effects. Apresenta-se resultado de estudo etnobotânico (fevereiro a agosto/2009) visando melhoramento e racionalização das práticas medicinais populares fundamentadas no uso de plantas. Foram aplicadas entrevistas semi-estruturadas a 220 famílias pertencentes à zona urbana do município de Mandaguaçu, Estado do Paraná. Durante as entrevistas foram registradas as seguintes informações das plantas utilizadas: nome comum, parte usada, modo de preparo, local de coleta, indicação terapêutica e efeitos adversos conhecidos. Adicionalmente, efetuou-se a análise comparativa dos dados obtidos nas entrevistas com os constantes na literatura pertinente para identificar incongruências de uso e aplicação. Dentre os entrevistados, 90% usam plantas medicinais, e as obtêm especialmente dos quintais. Foram registradas 44 citations etnobotânicas, englobando 47 espécies (22 famílias). As espécies mais citadas foram, respectivamente, Cymbopogon citrates (DC) Stapf. (capim cidreira), Mentha sp. (hortelã), Plectranthus barbatus Andrews (boldo) e Plectranthus ornatus Codd (boldo). As aplicações mais citadas foram para o tratamento de doenças do aparelho digestório (122 citations), aparelho respiratório (67) e sistema nervoso (40). Em geral, a população expressou adequado esclarecimento em relação ao modo de preparo das plantas que utilizam. No entanto, relatou desconhecer quaisquer efeitos adversos. Este panorama é preocupante, pois algumas espécies citadas são reconhecidas na literatura como potencialmente tóxicas ou responsáveis por efeitos adversos.